Longitudinal high-frequency ethnographic interviewing to simulate and prepare for intensive smartphone data collection among veterans with homeless experience - McInnes, D. Keith; Dunlap, Shawn; Fix, Gemmae M.; Foster, Marva V.; Conti, Jennifer; Roncarati, Jill S.; Hyde, Justeen K. (Frontiers in Digital Health, 2022)
OBJECTIVE: While Veteran homelessness has steadily declined over the last decade, those who continue to be unhoused have complex health and social concerns. Housing instability interferes with access to healthcare, social services, and treatment adherence. Preventing unwanted housing transitions is a public health priority. This study is the first of several phases that aim to develop smartphone-based interventions to improve the stability of veterans experiencing homelessness. In preparation for such interventions, we utilized ethnographic methods to identify essential data elements that must be collected to better understand (and eventually prevent) housing transitions and negative health events. METHODS: We used a case study design, selecting a small sample (n=10) of veterans representing a range of homelessness experiences. Participants were interviewed up to 14 times over a 4-week period, using a combination of qualitative methods. Additionally, 2 focus group discussions were conducted. Interviews were audio-recorded and transcribed. Data were synthesized and triangulated through use of rapid analysis techniques. RESULTS: Themes that were identified related to situations and behaviors that lead to housing instability and worsening health. Historical factors, such as child abuse and other traumas were commonly reported and provided an early pretext for homelessness in adulthood. Dynamic fluctuations in emotional states, relationships, and utilization of services were observed as were their impact on transitions in health and housing. We identified chains of events that unfold over time in which setbacks lead to frustration, then hopelessness and depression. These negative emotional states heightened vulnerability to Substance use, housing loss, and worsening mental and physical health. Most participants found the idea of smartphone interventions acceptable, as they may be able to capture real-time emotional states and factors influencing them. Major recommendations for improving engagement in smartphone-based research included attention to issues of trust, stigma, digital literacy, and physical design. CONCLUSION: The ethnographic approach used in this study provided valuable data to inform our future smartphone data collection effort. Data were critical to understanding aspects of day-to-day life that important to content development, app design, and approach to data collection.